ANALYSIS OF TEACHERS COMPETENCE IN DESIGNING A PORTFOLIO ASSESSMENT TECHNIQUES IN PRIMARY SCHOOL - Maesaroh, Fitroh (DIDAKTIKA TAUHIDI: JURNAL PENDIDIKAN GURU SEKOLAH DASAR, 2016)
The indicators in this pedagogical competence among teachers are able to master every assessment techniques and ways of designing assessment. The context of a teachers success in carrying out the assessment is inseparable from the quality of the draft assessment prepared. One design will be thorough assessment is a portfolio assessment. This study aims to determine how the competence of teachers in primary schools Objects in designing a portfolio valuation technique. This research method is descriptive qualitative. The results showed that the level of competence of teachers at SDN Benda in designing portfolio assessment techniques is 89,32%. This means that all classroom teachers at SDN Benda was able to design a portfolio with good ratings, but in designing a portfolio assessment that there are still shortcomings, such as lack of teacher attention to documents that will be used as a portfolio and lack of willingness of teachers in documenting the design of the portfolio is made in writing.